Efficacy and Safety of BoozLiv™ as an add on therapy in patients with alcoholic liver disease: An open-label, randomized controlled trial - Mohammad Nezamuddin Khan; Balavigneshwaran A; Priyadharshini Ananthathandavan; Vijayakumar T M; Rajesh N A; Pavithra A; Sumitha A (Gastroenterology & Endoscopy, 2024)
Background: Alcoholic Liver Disease (ALD) poses a significant global health threat, contributing to millions of deaths each year. Despite the well-established link between chronic alcohol consumption and liver damage, treatment options remain limited, emphasizing the need for innovative approaches. Methods: An open-label, randomized controlled trial was conducted in India, involving 68 adult ALD patients over a 12-week period. The patients were randomized into two groups: one receiving standard therapy and the other receiving standard therapy along with BoozLiv™ syrup. Liver function tests, Model for End-Stage Liver Disease (MELD) scores, and safety parameters were assessed at various intervals. Results: The study demonstrated that BoozLiv™ syrup, as an add-on therapy, significantly reduced total bilirubin, direct bilirubin, SGOT, SGPT, ALP, and GGT levels compared to standard therapy alone (p ​< ​0.05). The MELD score, indicative of liver function, showed a substantial improvement in the BoozLiv™ group (p ​< ​0.01). Safety analysis revealed that BoozLiv™ was well-tolerated, with only minor adverse effects such as nausea and vomiting reported. Conclusion: BoozLiv™ syrup, used in conjunction with standard therapy, showed promising results in improving liver function and reducing liver damage markers in ALD patients. The safety profile was favorable and no patient has withdrawn their consent due to adverse events. Further long-term studies in larger populations are warranted to validate these findings and establish BoozLiv™ as a potential therapeutic option for ALD.